Relevance of Volumetric Parameters Applied to [68Ga]Ga-DOTATOC PET/CT in NET Patients Treated with PRRT - Luca Urso; Angelo Castello; Giorgio Treglia; Stefano Panareo; Alberto Nieri; Ilaria Rambaldi; Matteo Caracciolo; Naima Ortolan; Licia Uccelli; Corrado Cittanti; Massimo Castellani; Mirco Bartolomei (Diagnostics, 2023)
Background: this study aims to explore the prognostic and predictive role of volumetric parameters on [68Ga]Ga-DOTATOC PET/CT in neuroendocrine tumors (NET) patients treated with peptide receptor radionuclide therapy (PRRT). Methods: We retrospectively evaluated 39 NET patients (21 male, 18 female; mean age 60.7 y) within the FENET-2016 trial (CTiD:NCT04790708). PRRT was proposed with [177Lu]Lu-DOTATOC alone or combined with [90Y]Y-DOTATOC. [68Ga]Ga-DOTATOC PET/CT was performed at baseline and 3 months after PRRT. For each PET/CT, we calculated SUVmax, SUVmean, somatostatin receptor expressing tumor volume (SRETV), and total lesion somatostatin receptor expression (TLSRE), as well as their percentage of changes (Δ), both for liver (_L) and for total tumor burden (_WB). Early clinical response (3 months after PRRT) and PFS were evaluated according to RECIST 1.1 and institutional NET board. Results: Early clinical response identified 9 partial response (PR), 25 stable disease (SD), and 5 progressive disease (PD). Post-SRETV_WB and ΔSRETV_WB were progressively increased among response groups (p = 0.02 and p = 0.03, respectively). Likewise, median post-SRETV_L was significantly higher in PD patients (p = 0.03). SUVmax and TLSRE did not correlate with early clinical response. Median PFS was 31 months. Patients with ΔSRETV_WB lower than −4.17% as well as those with post-SRETV_WB lower than 34.8 cm3 showed a longer PFS (p = 0.006 and p = 0.06, respectively). Finally, multivariate analysis identified ΔSRETV_WB as an independent predictor for PFS. Conclusions: our results could strengthen the importance of evaluating the burden of disease on [68Ga]Ga-DOTATOC PET/CT in NET patients treated with PRRT.